Introduction to Metal Matrix Composites Fabrication and Recycling - Nishida, Yoshinori; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
This book is the first of its kind to deal with fabrication processes of metal matrix composites (MMCs) theoretically, experimentally, systematically, and instructively. The theoretical bases of fabrication processes and recycling processes of MMCs are established in this volume. Most other books in the field are concerned with the mechanics of properties, which is not easy for readers to grasp, and they introduce fabrication processes only as techniques without theoretical discussion. Because this book provides a clear image of the fabrication processes of MMCs without using complicated mathematics, readers can use production theory to create new composites. Also, fundamental concepts of recycling of MMCs are given in this book for the first time so as to meet the demands for solving environmental problems. This work originally was published in Japanese and has attained a high reputation among Japanese professors and researchers in the field.
From the Contents: Fabrication processes for composites -- Fabrication by squeeze casting -- Theory of pressure infiltration -- Centrifugal casting of metal matrix composites -- Properties of composites -- Superplasticity of composites -- Materials for the fabrication of composites -- Recycling of composites.
Keywords: Machinery; Waste disposal; Materials; Materials Science; Ceramics, Glass, Composites, Natural Methods; Metallic Materials; Manufacturing, Machines, Tools; Waste Management/Waste Technology